Acrodermatitis continua of Hallopeau: a review and update on biological and small molecule targeted immunomodulatory therapies - Qiong Sun; Luyao Han; Zhimin Lin; Yuanhao Wu; Chen Li; Zhenhua Ying; Zhenhua Ying; Zhenhua Ying; Zuotao Zhao (Frontiers in Immunology)
Acrodermatitis continua of Hallopeau (ACH) is a rare aseptic pustular dermatosis for which clinical guidelines are lacking and treatment is largely based on case reports. Biologically targeted therapies offer new therapeutic ideas, with TNF antagonists such as adalimumab showing promising efficacy in both adults and children.The IL-17 and IL-23 axes play a key role in the pathogenesis of ACH, and anti-IL-17A and anti-IL-23 antibodies have shown therapeutic efficacy. In addition, new therapies such as IL-36 inhibitors and JAK inhibitors are being explored. Although biologics provide a new direction for ACH treatment, their safety and efficacy still need to be confirmed by large-scale clinical studies.